2013
DOI: 10.1039/c3tc30750f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanorods and graphene-like nanosheets by hot filament CVD: growth mechanisms and electron field emission

Abstract: Carbon nanorods and graphene-like nanosheets are catalytically synthesized in a hot filament chemical vapor deposition system with and without plasma enhancement, with gold used as a catalyst. The morphological and structural properties of the carbon nanorods and nanosheets are investigated by field-emission scanning electron microscopy, transmission electron microscopy and micro-Raman spectroscopy. It is found that carbon nanorods are formed when a CH 4 + H 2 + N 2 plasma is present while carbon nanosheets ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Hence, the synthesis and functionalization process of graphene are relatively complicated and high-cost, which limits its practical application. 59 Interestingly, 2D carbon nanosheets with graphene-like layered structure materials possess high electrical conductivity, a large number of active sites and high effective surface area, which make them ideal as an electrocatalyst support. 60,61 Many advanced techniques, including activation, helium ion bombardment, the template method, mechanical/chemical exfoliation, chemical vapour deposition, etc., have been developed to fabricate carbonaceous nanosheets but establishing an efficient and facile synthesis methodology for 2D porous carbon nanosheets would be of great benet for their large scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the synthesis and functionalization process of graphene are relatively complicated and high-cost, which limits its practical application. 59 Interestingly, 2D carbon nanosheets with graphene-like layered structure materials possess high electrical conductivity, a large number of active sites and high effective surface area, which make them ideal as an electrocatalyst support. 60,61 Many advanced techniques, including activation, helium ion bombardment, the template method, mechanical/chemical exfoliation, chemical vapour deposition, etc., have been developed to fabricate carbonaceous nanosheets but establishing an efficient and facile synthesis methodology for 2D porous carbon nanosheets would be of great benet for their large scale production.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we synthesized graphene‐like nanosheets using a layer of gold film as a catalyst in HFCVD and found that graphene‐like nanosheets can be easily synthesized under a catalyst without plasma . In consideration of the future applications of graphene‐like nanosheets in biology, it is better to grow them free of catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic methods of graphene and graphene-like materials include mechanical exfoliation 30 , reduction of chemically oxidized graphite 31,32 , thermal decomposition of SiC 33 , chemical vapor deposition 34,35 , exfoliation of graphite and graphite intercalated compounds 36 , solvothermal synthesis 37 . Unfortunately, all these methods are time-consuming, practically high-cost, relatively complicated and not environmentally-friendly 38,39 . Therefore, it is a critical challenge to exploit a facile and simple method to simultaneously fabricate graphene-like materials with high conductivity in large quantities.…”
Section: Introductionmentioning
confidence: 99%